Association between sequence variants in the FSHR gene and reproductive outcomes following IVF in predicted normoresponders. Issue 5 (May 2023) - Neves, Ana Raquel; Garcia, Sandra; Vuong, Lan TN; Blockeel, Christophe; Arroyo, Gemma; Spits, Claudia; Pham, Toan D; Ho, Tuong M; Tournaye, Herman; Polyzos, Nikolaos P
Highlights: c.919A>G genotypes AG/GG are associated with higher CPR versus genotype AA c.919A>G genotypes AG/GG are associated with higher LBR versus genotype AA c.2039A>G genotype GG is associated with lower CLBR versus genotype AA Abstract: Research question: Is there an association between FSHR sequence variants and reproductive outcomes following IVF in predicted normoresponders? Design: Multicentre prospective cohort study conducted from November 2016 to June 2019 in Vietnam, Belgium and Spain including patients aged <38 years, and undergoing IVF with a predicted normal response with fixed-dose 150 IU rFSH in an antagonist protocol. Genotyping was performed for three FSHR (c.919A>G, c.2039A>G, c.-29G>A) and one FSHB sequence variants (c.-211G>T). Clinical pregnancy rate (CPR), live birth rate (LBR) and miscarriage rate in the first embryo transfer and cumulative live birth rate (CLBR) were compared between the different genotypes. Results: A total of 351 patients underwent at least one embryo transfer. Genetic model analysis that adjusted for patient age, body mass index, ethnicity, type of embryo transfer, embryo stage and number of top-quality embryos transferred revealed a higher CPR for homozygous patients for the variant allele G of c.919A>G when compared to patients with genotype AA (60.3% versus 46.3%, adjusted odds ratio [ORadj] 1.96, 95% confidence interval [CI] 1.09–3.53). Also, c.919A>G genotypes AG and GG presented a higher CPR and LBR when compared with genotype AA (59.1% versus 46.3%, ORadj 1.80, 95% CI 1.08–3.00, and 51.3% versus 39.0%, ORadj 1.69, 95% CI 1.01–2.80, respectively). Cox regression models revealed a statistically significantly lower CLBR for c.2039A>G genotype GG in the codominant model (hazard ratio [HR] 0.66, 95% CI 0.43–0.99). Conclusion: These results demonstrate a previously unreported association between variant c.919A>G genotype GG and higher CPR and LBR in infertile patients and reinforce a potential role for genetic background in predicting the reproductive prognosis following IVF.